2020
DOI: 10.1007/s00167-020-06028-y
|View full text |Cite
|
Sign up to set email alerts
|

Better clinical outcomes and overall higher survival with hybrid versus cemented primary total knee arthroplasty: a minimum 15 years follow-up

Abstract: PurposeTo compare the clinical outcomes and survival at long‐term between hybrid and cemented primary total knee arthroplasty (TKA). A better clinical outcome and survival following a follow‐up as long as 15 years with the use of hybrid fixation as compared with cemented fixation was hypothesized. MethodsCase–control study of 126 patients with a mean age of 62.4 years who underwent hybrid TKA matched with 126 patients underwent cemented TKA. Clinical outcome was assessed by the Knee Society scores (KSS) and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A recent long-term follow-up study reported that KS, FS, and WOMAC in hybrid TKAs were signiicantly better than those in cemented TKAs at last follow-up (mean followperiod: 15.7 years in both hybrid and cemented TKAs), and pain might be the main reason for these diferences [4]. However, the mean diferences in Knee Society scores or WOMAC between groups were lower than the minimal clinically important diferences [17,18].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…A recent long-term follow-up study reported that KS, FS, and WOMAC in hybrid TKAs were signiicantly better than those in cemented TKAs at last follow-up (mean followperiod: 15.7 years in both hybrid and cemented TKAs), and pain might be the main reason for these diferences [4]. However, the mean diferences in Knee Society scores or WOMAC between groups were lower than the minimal clinically important diferences [17,18].…”
Section: Discussionmentioning
confidence: 96%
“…Theoretically, hybrid TKA would take advantages of the reliable and durable cementless ixation of the femoral component and eliminate the risk of tibial component loosening by cemented ixation. Many previous studies have reported satisfactory long-term results, including implant survival, of hybrid TKAs with modern prostheses [3][4][5].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The final functional outcomes were consistent with those reported in case series using hybrid [13, 15, 34] or cemented [21] stem fixation. However, patients who underwent revision TKA can be expected to have lower functional scores compared to primary TKA [23]. On the other hand, there was difficulty in removing the cement and the medullary restrictor in the patient of the cemented group who required re‐revision for subsequent aseptic tibial loosening.…”
Section: Discussionmentioning
confidence: 99%